2020
DOI: 10.3389/fmicb.2020.00072
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Burkholderia pseudomallei Genes Induced During Infection of Macrophages by Differential Fluorescence Induction

Abstract: Burkholderia pseudomallei, the causative agent of melioidosis, can survive and replicate in macrophages. Little is known about B. pseudomallei genes that are induced during macrophage infection. We constructed a B. pseudomallei K96243 promoter trap library with genomic DNA fragments fused to the 5 end of a plasmid-borne gene encoding enhanced green fluorescent protein (eGFP). Microarray analysis showed that the library spanned 88% of the B. pseudomallei genome. The recombinant plasmids were introduced into Bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Most of these genes were located on chromosome 2 and associated with adaptation to and survival in intracellular environments (Ong et al 2004 ). Two genes, bpss1622 (a type III secretion system cluster 2 component) and bpss2104 (a T4SS cluster 3 component) were selected for deletion as they had not been studied previously (Jitprasutwit et al 2020 ). Infection of G. mellonella larvae with Δ bpss1622 or Δ bpss2104 resulted in attenuation, although the potential underlying mechanism(s) were not discussed (Jitprasutwit et al 2020 ).…”
Section: Burkholderia Pseudomallei and Burkholderi...mentioning
confidence: 99%
“…Most of these genes were located on chromosome 2 and associated with adaptation to and survival in intracellular environments (Ong et al 2004 ). Two genes, bpss1622 (a type III secretion system cluster 2 component) and bpss2104 (a T4SS cluster 3 component) were selected for deletion as they had not been studied previously (Jitprasutwit et al 2020 ). Infection of G. mellonella larvae with Δ bpss1622 or Δ bpss2104 resulted in attenuation, although the potential underlying mechanism(s) were not discussed (Jitprasutwit et al 2020 ).…”
Section: Burkholderia Pseudomallei and Burkholderi...mentioning
confidence: 99%
“…The second stage of the intracellular life cycle involves Bpm replicating within the cytoplasm and the mobilization of host actin, while evading and/or subverting the bactericidal pathways being activated within the host cell. A recent study [ 17 ] demonstrated that Bpm upregulates genes associated with combating oxidative stress once free in the cytoplasm. This agrees with another study [ 18 ], that showed that Bpm induces host factor heme oxygenase 1 (HO-1), which corrals Reactive Oxygen Species (ROS) and promotes host cell survival.…”
Section: Bpm Pathogenesis Process Leading To Mnmentioning
confidence: 99%
“…2 ). Expression profile of BPSL1661 was obtained from Ooi et al and cross-checked for consistency with ( Rodrigues et al 2006 ; Chin et al 2015 ; Jitprasutwit et al 2020 ) where conditions were overlapped.…”
Section: Methodsmentioning
confidence: 99%